Kontribusi Cendekiawan Muslim Lokal Bagi Pembangunan Pendidikan Indonesia - Mustari Bosra (Society, 2022)
Education is an urgent matter in every culture and civilization. With education, mankind can change themselves and their civilization. The same is true for the process of spreading Islam in Indonesia. Since Islam was first introduced in Indonesia, its spreading has been inseparable from people’s daily lives, including the building and shaping of the education sector (Rochmawati et al., 2018; Vickers, 2013; Hasan, 2009). Java Island is one of Indonesia’s regions with a wider history of Islamic education (Ricklefs, 2012; Woodward, 2010). In the present manuscript, the author examines the contribution of Muslim scholars in developing Indonesia’s modern education. Data were collected from both primary and secondary sources. The mediator and social agency method has been used to facilitate the investigation. The author conducted a structural study that reconstructs historical events and occurrences regarding educational development and transformation in the country. The study’s findings are based on the question, “What is the contribution of Muslim Scholars in the development of Indonesia’s modern education, and how is the education process on Java Island? This question laid the foundation for this study, and it helps to understand the functions of local Muslim scholars in the development of education between the 19th and 20th centuries in the Indonesian archipelago. The findings show that the characteristics of Muslim scholars’ movements regarding education on Java Island consist of mainly two stages. Firstly, education is conducted at mosques, which later developed into Islamic schools classified as madrasahs and pesantren (Azra, 2018). In the second stage, education efforts are converted from its form of Islamic schools into Islamic organizations, leading to the establishment of several educational institutions and public schools, ranging from kindergarten to higher education (Daulay & Tobroni, 2017; Azra, 2015). Finally, it concludes that Indonesia’s education developed in stages, from education at mosques and small community gatherings in residences of Muslim scholars to Islamic schools. Finally, Islamic organizations were formed to develop today’s public education system.